Place of caregiver who accompanies a person with Alzheimer's disease or related, what should be their role - Nour, Mhamed; Renaud, Jean; Gardoni, Mickael (Advances in Social Sciences Research Journal, 2018)
Alzheimer's disease or related diseases hits very hard the society. With alarming statistics and an absence so far, of curative and preventive solution, the non-drug approach nonetheless improves the quality of life of patients by allowing them to regain more autonomy, memory and so on and therefore likely to delay the advancement of the symptoms of the disease. The solution that seems most promising would be to develop a "helping-assisted" momentum that should help protect the caregiver in a more appropriate climate with the caregiver. In this article, we want to redefine the role of the caregiver, missions, but also his needs, when accompanying a person with the disease. Thus, we suggest the use of an "Intelligent and shared" booklet that will help manage this dynamic of the helping - helped couple. This "Smart and Shared" notebook would be computerized to answer certain requests concerning home activities, the medical aspect, the follow-up of the patient, the reports of the non-medical sessions and other activities in medical environment or at home. This connected notebook, once produced, could represent a robust and reliable assistance for the Near Career in his activities of accompaniment of the helped.